Outcome of Aspiration Alone and Aspiration with Instillation of Steroid in Ganglion Cyst of Wrist- A Comparative Study - Sazal, Hafizur Rashid; Haque, Nazmul; Rahman, Nashid; Rezwan, ASM; Afroz, Chamina (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Ganglion cysts are common soft tissue swellings of hand and wrist. Main concerns patients have are the cosmetic appearance and the fear of future malignancy. Various modalities of treatment are available but known to have high rate of recurrence. Here we study mainly the recurrence rate after aspiration alone and aspiration with instillation of steroid, to compare these minimally invasive procedures that can help to treat and give symptomatic relief from this commonly occurring problem. Methodology: A Prospective, Comparative study was carried out with purposive sampling to include all patient of Ganglion cyst of wrist. After detail counseling, Patient desired among Aspiration only and Aspiration with instillation of Steroid randomly. All cases were followed up on 3rd, 6th and 12th month. Recurrence data were collected and all data were arranged and analyzed. Result: Total 113 patients were included in our study, Male female ratio was 1:1.3, Mean age was 31.3 years. 74(65.5%) patient had ganglion on right wrist and 39 (34.5%) patient had it on left wrist. Dorsal ganglion was 89 (78.8%) and Volar ganglion was 24 (21.2%). In this study 58 (51.3%) patient underwent Aspiration alone, among them total 22 (37.9%) had recurrence. 12 (20.7%) had recurrence of the ganglion within 3 months, followed by 6(10.3%) within 6 month and 4 (6.9%) within 12 month. Aspiration with instillation of steroid was done in 55 (48.7%) patients. Recurrence within 1 year was found in total 16 (29.1%) cases. 4 (7.3%) had recurrence within 3 month and 6 (10.9%) cases each had recurred within 6 and 12 month respectively. Dorsal and Volar ganglion had similar recurrence rate i.e 33% irrespective of type of procedure. Conclusion: We may conclude that Aspiration with instillation of steroid had better outcome than Aspiration alone but both have significant recurrence rate. J Bangladesh Coll Phys Surg 2023; 41: 108-113